PENGEMBANGAN PERANGKAT PELATIHAN KEPRAMUKAAN BERBASIS PENDEKATAN KONTEKSTUAL PADA TINGKAT PENGGALANG DI SD IT AL BASHIRAH KOTA PALOPO - Inna, Mudma; Hisbullah; Arwan Wiratman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to develop a contextual approach-based Scout training kit for the Penggalang (Junior Scout) level at SD IT Al Bashirah, Palopo City, and to determine its validity and practicality. The study employs the Research and Development (R&D) method using the 4D development model, comprising the define, design, develop, and disseminate stages. The research subjects consisted of Scout leaders and Penggalang-level students, while the research object was the contextual approach-based Scout training kit. Data were collected through observation, interviews, questionnaires, and documentation, and subsequently analyzed both qualitatively and quantitatively. The results indicate that Scout activities lacked training materials that were systematically organized and aligned with student needs. The developed kit includes training objectives, content, practical activities, student worksheets, educational games, reflection exercises, and guidelines for leaders. Validation results from design, content, and language experts yielded scores of 75% (valid), 97.5% (highly valid), and 90% (highly valid), respectively. Practicality test results showed a 93.75% response rate from leaders and 94% from students, both falling into the